Characteristic of Tumor Regrowth After Gamma Knife Radiosurgery and Outcomes of Repeat Gamma Knife Radiosurgery in Nonfunctioning Pituitary Adenomas - Li, Yanli; Wu, Lisha; Quan, Tingting; Fu, Junyi; Cao, Linhui; Li, Xi; Liang, Shunyao; Huang, Minyi; Deng, Yinhui; Yu, Jinxiu (Frontiers in Oncology, 2021)
Objective: The aim of this study was to report the characteristic of tumor regrowth after gamma knife radiosurgery (GKRS) and outcomes of repeat GKRS in nonfunctioning pituitary adenomas (NFPAs). Design and Methods: This was a single-center retrospective study of 369 NFPA patients treated with GKRS. The median age was 45.2 (range, 7.2-84.0) years. The median tumor volume was 3.5 (range, 0.1-44.3) cm3, and the median margin dose was 13.0 (range, 8.0-22.0) Gy. Results: Twenty-four patients (6.5%) were confirmed as regrowth after GKRS. In multivariate analysis, parasellar invasion and margin dose (<12 Gy) were associated with tumor regrowth (hazard ratio [HR]=3.125, 95% confidence interval [CI]=1.318-7.410, p=0.010 and HR=3.359, 95% CI=1.347-8.379, p=0.009, respectively). The median time of regrowth was 86.1 (range, 23.2-236.0) months. Previous surgery was associated with tumor regrowth out of field (p=0.033). Twelve patients underwent repeat GKRS, including regrowth in (n=8) and out of field (n=4). Tumor shrunk in 7 patients (58.3%), remained stable in 1 (8.3%) and regrowth in 4 (33.3%) with a median repeat GKRS margin dose of 12 (range, 10.0-14.0) Gy. The actuarial tumor control rates were 100%, 90%, 90%, 68% and 68% at 1, 3, 5, 10 and 15 years after repeat GKRS respectively. Conclusions: Parasellar invasion and tumor margin dose (<12Gy) were independent risk factors for tumor regrowth after GKRS. Repeat GKRS might be effective on tumor control for selected patients. For regrowth in field due to relatively insufficient radiation dose, repeat GKRS might offer satisfactory tumor control. For regrowth out of field, preventing regrowth out of field was the key management. Sufficient target coverage and close follow-up might be helpful.